2015
DOI: 10.1111/nan.12292
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in frontotemporal lobar degeneration and motor neurone disease associated with expansions in C9orf72 is linked to TDP‐43 pathology and not associated with aggregated forms of dipeptide repeat proteins

Abstract: AimsA hexanucleotide expansion in C9orf72 is the major genetic cause of inherited behavioural variant Frontotemporal dementia (bvFTD) and motor neurone disease (MND), although the pathological mechanism(s) underlying disease remains uncertain.MethodsUsing antibodies to poly‐GA, poly‐GP, poly‐GR, poly‐AP and poly‐PR proteins, we examined sections of cerebral cortex, hippocampus, thalamus, cerebellum and spinal cord, from 20 patients with bvFTD and/or MND bearing an expansion in C9orf72 for aggregated deposits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 35 publications
(127 reference statements)
9
72
0
Order By: Relevance
“…Inclusions of unconventionally translated DPRs from both sense (poly-GP, poly-GA, and poly-GR) and antisense (poly-GP, poly-PA and poly-PR) strand RNA repeats are well-known neuropathological hallmarks of C9 ALS [3, 9, 14, 30, 31, 36, 45, 60]. We assessed the five unique DPRs in C9 ALS nervous system using DPR-specific antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusions of unconventionally translated DPRs from both sense (poly-GP, poly-GA, and poly-GR) and antisense (poly-GP, poly-PA and poly-PR) strand RNA repeats are well-known neuropathological hallmarks of C9 ALS [3, 9, 14, 30, 31, 36, 45, 60]. We assessed the five unique DPRs in C9 ALS nervous system using DPR-specific antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aggregations of all five DPR proteins have been observed in C9 ALS nervous systems [3, 14, 36, 60]. However, several studies have shown that TDP-43 pathology rather than DPR pathology correlates to neurodegeneration [9, 30, 31, 45]. Neuropathological evidence of intra-nuclear accumulation such as dot-like aggregates of arginine-containing poly-GR or poly-PR DPRs that would support their nuclear toxicity has been controversial, with some reports supporting their presence [32, 45, 52], and others suggesting non-specificity [9, 31, 36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our data not only indicate that expression of poly(GA) is sufficient to induce neurodegeneration, but also that insoluble forms of the protein (i.e., oligomers or aggregates) are the toxic culprit. Given that the frequency of poly(GA) inclusions associates with cortical neurodegeneration only moderately 27 if at all 28,46 , it seems likely that oligomers are the more likely effector, as is suspected to be the case for other aggregation-prone proteins in neurodegenerative disorders 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Several additional studies have similarly shown that DRP burden is not well-correlated with degeneration (Mackenzie et al , 2013; Davidson et al , 2015; Schludi et al , 2015). This is in contrast to TDP-43-positive inclusions, which are most abundant in the most severely affected brain regions (Mackenzie et al , 2013; Davidson et al , 2015; Mackenzie et al , 2015). …”
Section: Ran Translation At Ggggcc and Ggcccc Repeats In C9 Als/ftdmentioning
confidence: 96%